CONTRIBUTING FACTORS OF SUICIDAL IDEATION AMONG MALAYSIAN PUBLIC UNIVERSITY - Iszati Afiqah, Iskandar Zulkarnain (Universiti Malaysia Sarawak (UNIMAS), 2021)
Background: Suicidal ideation is viewed as a significant forerunner to later attempted and committed suicide and is of significant general mental health importance. In Malaysia, nationwide representative information on suicidal ideation is as yet deficient. Even though many studies have been directed about suicidal behavior, there is as yet limited and deficient information about suicidal ideation as far as contributing components like perfectionism, stress, and loneliness and barely so on the explicit group of people like university students. Objectives: To investigate the contributing factors associated with suicidal ideation among university students of University Malaysia Sarawak. Method: Random sampling method was used to select UNIMAS students to yield a total number of 245 participants. Questionnaires were distributed by google form through WhatsApp and Instagram to collect data. Independent Sample t-Test was used to answer research question number 1. One-Way ANOVA was used to answer research question number 2, while Multiple Linear Regression was conducted to answer research question number 3. Ethics were followed by the researcher along the journey. Results: Based on these findings, there is no significant difference in suicidal ideation based on gender. In addition, the findings found that the male participants had a greater mean score than female participants in perfectionism and loneliness, while female participants had a greater mean score than male participants in terms of stress. The findings also revealed that viii perfectionism and stress were statistically significantly lower after taking FCSHD compared to The FENG. In terms of loneliness, there was no statistically significant difference between groups. Loneliness was accounted for the most prevalent contributing factor associated with suicidal ideation among university students of UNIMAS, stress yielded the second prevalent contributing factor and the third prevalent contributing factor was perfectionism.